A Multiple Criteria Approach for Negotiating Ecosystem Services Supply Targets and Forest Owners’ Programs - Borges, Jose (2017)
Land tenure heterogeneity may be an obstacle to forested landscape-level management planning and the provision of ecosystem services. This research focused on the potential of combining participatory workshops and multiple criteria decision methods (MCDMs) to support the development and negotiation of targets for the supply of ecosystem services and help design the management plan needed to meet those targets. We describe an application to two forested landscapes with several ownership types in Portugal. The approach encompassed the design of two workshops involving more than 40 stakeholders (forests owners, the forest service, the forest industry, local municipalities and other nongovernmental organizations). The list of ecosystem services included carbon stocks, cork, pine cones, and forest inventory at the end of the planning horizon as well as volume flows from a range of forest species. Results demonstrated the potential of MCDM tools to help individual forest stakeholders set and adjust ecosystem services target levels. They further demonstrated the potential of MCDMs to facilitate the negotiation of these targets by the stakeholders and the reaching of meaningful solutions. Finally, they demonstrated that these tools provide valuable information to combine the negotiations of both targets and behaviors and programs needed to attain them.